Globalization and Utopia
XI, 275 p.
Keywords: Taking aim at the belief in utopia's demise, this collection of original essays offers a new look at the vibrant renewal of utopianism emerging in response to the challenges of globalization. It consider questions of hope and transformation associated with the utopian desire for social change.